Metformin inhibits proliferation and migration of glioblastoma cells independently of TGF-β2. Issue 13 (2nd July 2016) - Seliger, Corinna; Meyer, Anne-Louise; Renner, Kathrin; Leidgens, Verena; Moeckel, Sylvia; Jachnik, Birgit; Dettmer, Katja; Tischler, Ulrike; Gerthofer, Valeria; Rauer, Lisa; Uhl, Martin; Proescholdt, Martin; et al.
ABSTRACT: To this day, glioblastoma (GBM) remains an incurable brain tumor. Previous research has shown that metformin, an oral anti-diabetic drug, may decrease GBM cell proliferation and migration especially in brain tumor initiating cells (BTICs). As transforming growth factor β 2 (TGF-β2 ) has been reported to promote high-grade glioma and is inhibited by metformin in other tumors, we explored whether metformin directly interferes with TGF-β2 -signaling. Functional investigation of proliferation and migration of primary BTICs after treatment with metformin+/−TGF-β2 revealed that metformin doses as low as 0.01 mM metformin thrice a day were able to inhibit proliferation of susceptible cell lines, whereas migration was impacted only at higher doses. Known cellular mechanisms of metformin, such as increased lactate secretion, reduced oxygen consumption and activated AMPK-signaling, could be confirmed. However, TGF-β2 and metformin did not act as functional antagonists, but both rather inhibited proliferation and/or migration, if significant effects were present. We did not observe a relevant influence of metformin on TGF-β2 mRNA expression (qRT-PCR), TGF-β2 protein expression (ELISA) or SMAD-signaling (Western blot). Therefore, it seems that metformin does not exert its inhibitory effects on GBM BTIC proliferation and migration by altering TGF-β2 -signaling. Nonetheless, as low doses of metformin are able to reduce proliferation of certain GBM cells, further exploration of predictors of BTICs' susceptibility to metformin appears justified.